Utilization of sludge palm oil as a novel substrate for biosurfactant production - Wan Nawawi, Wan Mohd Fazli; Jamal, Parveen; Alam, Md. Zahangir (Elsevier, 2010)
This paper introduces sludge palm oil (SPO) as a novel substrate for biosurfactant production by liquid state fermentation. Potential strains of microorganism were isolated from various hydrocarbon-based sources at palm oil mill and screened for biosurfactant production with the help of drop collapse method and surface tension activity. Out of 22 isolates of microorganism, the strain S02 showed the highest bacterial growth with a surface tension of 36.2 mN/m and was therefore, selected as a potential biosurfactant producing microorganism. Plackett–Burman experimental design was employed to determine the important nutritional requirement for biosurfactant production by the selected strain under controlled conditions. Six out of 11 factors of the production medium were found to significantly affect the biosurfactant production. K2HPO4 had a direct proportional correlation with the biosurfactant production while sucrose, glucose, FeSO4, MgSO4, and NaNO3 showed inversely proportional relationship with biosurfactant production in the selected experimental range.